(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
Cereal crops, including wheat (Triticum aestivum), are among the most important vital and strategic crops in the world because they contain important food sources of vitamins, proteins, carbohydrates, fats, and other nutrients. Stored grains are affected by many insect pests, causing significant economic losses in grain weight that may reach 10% in one storage season. One of the most dangerous stored insects that infest grains is the hairy grain beetle (Trogoderma granarium). The insect is known for its resistance to various liquid and gaseous chemical pesticides, as well as its ability to withstand long periods of drought and high temperatures. This adaptability has facilitated its spread across different countries and enabled it to conquer new geographical areas. Several methods have been employed to combat this insect, with chemical control being the most prominent. However, the use of chemical pesticides has resulted in negative environmental impacts and challenges in addressing the various roles insects play. Due to the economic significance of the hairy grain beetle and the need to minimize reliance on harmful chemical pesticides, plant extracts and nano-preparations of iron from the leaves of the oleander plant (Nerium oleander) were utilized. These compounds have shown high effectiveness in controlling the Khabra insect in both laboratory and storage environments, while also being environmentally safe.